Indian tribes and the mainstream - Chaudhury, Sukant K.; Patnaik,Soumendra Mohan (Published on behalf of Ethnographic & Folk Culture Society, Lucknow [by] Rawat Publications, 2008)
Contributed articles presented at the National Seminar on "Tribes and the Mainstream of Indian Society and Culture" at Lucknow in 1994.